Effect of Al Concentration on Structural, Optical and Electrical Properties of (Gd, Al) Co-Doped ZnO and Its n-ZnO/p-Si (1 0 0) Heterojunction Structures Prepared via Co-Sputtering Method - Raship, Nur Amaliyana; Mohd Tawil, Siti Nooraya; Nayan, Nafarizal; Ismail, Khadijah (Mdpi, 2023)
Heterojunction structures of n-ZnO/p-Si were prepared through the growth of undoped ZnO and (Gd, Al) co-doped ZnO films onto p-type Si (1 0 0) substrates, using a co-sputtering method. The structural and optical properties of the Gd-doped ZnO films were studied as a function of different Al doping concentrations. The X-ray diffraction profiles indicated that the films had a nanocrystalline structure of ZnO with a (0 0 2) preferential orientation. An increase in the Al doping concentration deteriorated the (0 0 2) diffraction peak intensity. The transmittance measurements in the UV–Vis wavelength range indicated that the film’s optical gap increased with increase in Al doping concentration. The heterojunction parameters were evaluated using the current–voltage (I-V) characterization carried out of the fabricated n-ZnO/p-Si heterostructure, in dark conditions at room temperature. From these measurements, the n-ZnO-based DMS/p-Si heterojunction diode with the use of (Gd, Al) co-doped ZnO film showed the lowest leakage current of 1.28 × 10−8 A and an ideality factor η of 1.11, close to the ideal diode behavior of η = 1, compared to the n-Gd-doped ZnO/p-Si and n-undoped ZnO/p-Si heterojunction diodes.